Kevalidan Perangkat Pembelajaran Model Cooperative Learning Tipe Jigsaw Pada Materi Keanekaragaman Hayati - Herinda Mardin (Peneliti.net, 2022)
The effectiveness and achievement of learning objectives is determined by the teacher. The teacher must design the lesson plans before the learning activities take place. This study aims to develop lesson plans based on the JigSaw type cooperative learning model for quality biodiversity materials based on the level of validity. The research only focuses on testing the validity of learning devices. The final result of this research is to produce a valid lesson plan learning device product. To determine the level of validity of this research tool through the expert validation stages (expert learning tools). This expert test (validation) is carried out by 4 validators who are lecturers and experts in the field of education, there are 8 aspects that are assessed in the lesson plan. The results showed that the level of validity of the lesson plan with the cooperative learning jigsaw model from expert validation was quite valid with an average value of 3.2.